COMPARATIVE STUDY OF WATER RESCUE OCCURRENCES ON TWO BEACHES OF FORTALEZA - Barbosa Filho, Ruy Paulino; Crisóstomo, Vicente Lima; Freitas, Eduardo Benevides de (Geosaberes; Vol 12 (2021), 2021)
The role of the Military Fire Department in the prevention and rescue of drowning victims reveals that knowing local realities is crucial to the decision making process in the management of this service. This paper presents a study in important areas of the coast of Fortaleza, “Praia do Futuro” and “Caça e Pesca”, popular leisure destinations for residents and tourists. The objective of this work is to compare the two abovementioned areas, regarding the rescue of people in situation of danger or drowning, taking into account the situation of tides. The sample consists of records of 156 days with some occurrence in 2017. The results indicate that the tidal coefficient has greater oscillation in “Praia do Futuro” and is related to the number of occurrences which is higher in this beach as expected. The most frequent victims are young males, ages between 10 to 29 years old.